2014
DOI: 10.1186/1475-2891-13-20
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effect and safety of ginger in the treatment of pregnancy-associated nausea and vomiting

Abstract: Background and objectivesNausea and vomiting during pregnancy (NVP) occur commonly. Possible harmful side-effects of conventional medicine to the fetus create the need for alternative options to relieve NVP. This systematic review (SR) investigated current evidence regarding orally administered ginger for the treatment of NVP. The primary objective was to assess the effectiveness of ginger in treating NVP. The secondary objective was to assess the safety of ginger during pregnancy.MethodsA comprehensive electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
1
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(145 citation statements)
references
References 21 publications
2
126
1
16
Order By: Relevance
“…All authors were involved in the dissemination of the survey study. (8) All values presented as n (column%) All values presented as row%(n) M A N U S C R I P T A lack of interest in this area 3 (6) M A N U S C R I P T…”
Section: Authors' Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…All authors were involved in the dissemination of the survey study. (8) All values presented as n (column%) All values presented as row%(n) M A N U S C R I P T A lack of interest in this area 3 (6) M A N U S C R I P T…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…homeopathy), [2] the use of dietary supplements for an extensive range of specific conditions including, but not limited to, hypertension, antibiotic-associated diarrhea, morning sickness, and in the critically ill have shown promise. [3][4][5][6][7] However, while there has been a significant amount of published literature investigating the attitudes and levels of knowledge of healthcare practitioners regarding CAM [8][9][10][11][12], dietary supplements alone have not been well explored.…”
Section: Introductionmentioning
confidence: 99%
“…The plants used in this study have been shown to be safe to use up to doses as large as 1gram [38][39][40][41] . Giving such high doses chronically may however have dire consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Diese Hemmung korreliert mit den Ergebnissen der bereits oben genannten Studie zur Motilität mit Padma Lax [20]. Ferner ist Ingwer für seine antiemetischen, karminativen und spasmolytischen Eigenschaften bekannt [26][27][28][29].…”
Section: Experimentelle Datenunclassified